The affect system has parallel and integrative processing components: form follows function. - Cacioppo, John T.; Gardner, Wendi L.; Berntson, Gary G. (Journal of Personality & Social Psychology, 1999)
The affect system has been shaped by the hammer and chisel of adaptation and natural selection such that form follows function. The characteristics of the system thus differ across the nervous system as a function of the unique constraints existent at each level. For instance, although physical limitations constrain behavioral expressions and incline behavioral predispositions toward a bipolar (good–bad, approach–withdraw) organization, these limiting conditions lose their power at the level of underlying mechanisms. According to the authors' model of evaluative space (J. T. Cacioppo & G. G. Berntson, 1994; J. T. Cacioppo, W. L. Gardner, & G. G. Berntson, 1997), the common metric governing approach-withdrawal is generally a single dimension at response stages that itself is the consequence of multiple operations, such as the activation function for positivity (appetition) and the activation function for negativity (aversion), at earlier affective processing stages. Reprinted by permission of the publisher.